The laboratory approach in the diagnosis of systemic autoinflammatory diseases - B. Frediani; M. Galeazzi; O.M. Lucherini; G.D. Sebastiani; D. Rigante; M.G. Brizi; L. Cantarini (PAGEPress Publications, 2011)
Systemic autoinflammatory diseases are a group of inherited disorders of the innate immunity characterized by the recurrence of febrile attacks lasting from few hours to few weeks and multi-district inflammation of different severity involving skin, serosal membranes, joints, gastrointestinal tube and central nervous system. The vast majority of these conditions is caused by mutations in genes involved in the control of inflammation and apoptosis mechanisms. The group includes familial Mediterranean fever, mevalonate kinase deficiency syndrome, tumor necrosis factor receptor-associated periodic syndrome, cryopyrin-associated periodic syndromes, hereditary pyogenic and granulomatous disorders. Their diagnostic identification derives from the combination of clinical and biohumoral data, though can be sometimes confirmed by genotype analysis.